Unterrichtsforschung und Unterrichtspraxis im Gespräch Interkulturelle und interprofessionelle Perspektiven auf eine Unterrichtsstunde - Hallitzky, Maria; Kieres, Christine; Kinoshita, Emi; Yoshida, Nariakira (Verlag Julius Klinkhardt, 2022)
This volume documents and reflects on an intercultural and interprofessional exchange about teaching between schools and classroom research. A teacher from Germany opens her classroom to the videographic observations of a Japanese and a German research group. In order to build bridges between the different fields of work related to the same object - the teacher's teaching - the researchers and the teacher open their analytical perspectives of teaching to each other. The volume maps discursive border crossings between an action-oriented didactic, a qualitative-reconstructive and a development-oriented view of the Japanese Jugyo Kenkyu (Lesson Study), in which the different professional cultures meet without intervening transformatively in each other's fields. The different perspectives invite to perceive ideas and concepts of teaching and its research with other than the usual readings and to productively introduce related irritations into the debates about the research and development of teaching.